2018
DOI: 10.1002/asia.201800185
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Evolution of Koneramine Complexes from One‐Pot Reactions: Snapshots of Intermediates Offer Facile Routes to New Dipicolylamines

Abstract: Koneramines (L OR', R=Ph or Ts; R'=Me, iPr) and their complexes were found to emerge from the system of pyridine-2-carboxaldehyde and N-phenyl/tosylethylenediamine when a primary or secondary alcohol was used as solvent. Imidazolidinylpyridines (L , R=Ph or Ts) became major emergents whereas hemi-aminals (L OH, R=Ph or Ts) are minor emergents of the system when tertiary butanol was used as the solvent; the bulky tertiary butyl group prevented the addition of alcohol to the iminium ion that diverted the equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…1). Furthermore we report the post-assembly modification of the fragile hemiaminal ether linkages 16 The formation of aforementioned complexes indicated that the HAE formation works in any primary and secondary alcohols and thiols except tertiary alcohols.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…1). Furthermore we report the post-assembly modification of the fragile hemiaminal ether linkages 16 The formation of aforementioned complexes indicated that the HAE formation works in any primary and secondary alcohols and thiols except tertiary alcohols.…”
Section: Introductionmentioning
confidence: 90%
“…13 Our one-pot protocol allowed the stereoselective (syn or anti) and geometry specific (facial or meridional) assembly of hemiaminal ether ligands (L R OR') comprising 2,2'dipicolylamine backbone in good yield from prebiotically relevant multicomponent pool of mono-N-substituted ethylenediamines, pyridine-2-carboxaldehyde and primary alcohols or thiols at ambient conditions. [14][15][16][17] Although the multicomponent mixture contained both syn (RR and SS) and anti (RS and SR) forms of hemiaminal ether L R OR' is in dynamic equilibrium with plethora of other components such as hemiaminal and imidazoline, we succeeded to trap syn-L R OR' as complexes with Cu(II) and Zn(II) ions and anti-L R OR' by employing Ni(II) and Cd(II) ions.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Our one-pot protocol allowed the stereoselective (syn or anti) and geometry specific (facial or meridional) assembly of hemiaminal ether ligands (L R OR') comprising 2,2'-dipicolylamine backbone in good yield from prebiotically relevant multicomponent pool of mono-N-substituted ethylenediamines, pyridine-2-carboxaldehyde and primary alcohols or thiols at ambient conditions. [6][7][8][9] Although the multicomponent mixture contained both syn (RR and SS) and anti (RS and SR) forms of hemiaminal ether L R OR' in dynamic equilibrium with plethora of other components such as hemiaminal and imidazoline, we succeeded to trap syn-L R OR' as complexes with Cu(II) and Zn(II) ions and anti-L R OR' by employing Ni(II) and Cd(II) ions. Hemiaminal or hemiaminal ether moieties are known to be Achilles' heel and seldom isolated as part of cyclic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently reported a new family of potential tridentate ligands known as koneramines, [20][21][22] which contain a 2,2′-dipicolylamine scaffold. Initially, koneramines were stereoselectively self-assembled from a multicomponent onepot reaction of mono-N-substituted ethylenediamine and pyridine-2-carbinal in alcohol/thiol.…”
Section: Introductionmentioning
confidence: 99%